Manajemen program sekolah bilingual tingkat Sekolah Dasar Islam - Muawanah, Siti (Tawazun: Jurnal Pendidikan Islam, 2023)
The bilingual school program at SDIT Al Ikhlas Bekasi has a management design that involves the formation of a bilingual team, English language training for teachers, and the addition of conversation lessons. Organizing is done by the curriculum development team, and program implementation involves using bilingual language in learning and daily activities. Although there are methods such as vocabulary memorization tasks, conversation deposits, and habituation to communicate in English, obstacles arise from the lack of infrastructure and teacher abilities. Program evaluation includes classroom supervision, performance supervision, and formative and summative evaluations for students. This study used a qualitative approach with data collection techniques such as interviews, observations, and documentation studies. The results show that the bilingual program at SDIT Al Ikhlas has been well organized, although it faces obstacles in implementation and evaluation. Abstrak Program sekolah bilingual di SDIT Al Ikhlas Bekasi memiliki desain manajemen yang melibatkan pembentukan tim bilingual, pelatihan bahasa Inggris bagi guru, dan penambahan pelajaran conversation. Pengorganisasian dilakukan oleh tim pengembang kurikulum, dan implementasi program melibatkan penggunaan bahasa bilingual dalam pembelajaran dan kegiatan sehari-hari. Meskipun ada metode seperti tugas menghafal vocabulary, setoran conversation, dan pembiasaan berkomunikasi dalam bahasa Inggris, kendala muncul dari kurangnya sarana prasarana dan kemampuan guru. Evaluasi program mencakup supervisi kelas, supervisi kinerja, dan evaluasi formatif dan sumatif untuk siswa. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data seperti wawancara, observasi, dan studi dokumentasi. Hasilnya menunjukkan bahwa program bilingual di SDIT Al Ikhlas telah diorganisir dengan baik, meskipun menghadapi kendala dalam implementasi dan evaluasi.